High performance of chromium recovery from aqueous waste solution using mixture of palm-oil in emulsion liquid membrane - Othman, N. (Elsevier Ltd, 2016)
Industrial effluent containing metal ions especially from semiconductor industry is considered as a serious environmental pollutant. A green emulsion liquid membrane (ELM) has been formulated in this research using an environmental-friendly refined palm oil as the main diluent of ELM to recover the chromium from wastewater. The feasibility of using palm oil-based ELM for chromium extraction and its stability were investigated. Several parameters, including carrier concentration, agitation speed, internal phase concentration, treat ratio, and agitation time, which could affect the extraction and recovery performance of chromium in ELM process, were attempted. The results showed that 0.2M of TOMAC, 600rpm for agitation speed and 1.0M of NaOH, 2:1 for treat ratio provided enhancement of emulsion stability and almost 100% of chromium was extracted and recovered.